Construction of a multienzyme cascade reaction system and its application in D-tagatose biosynthesis - Xiaoxiao Zhang; Jie Chu; Yuanqiang Lv; Xuan Li; Aijiao Yin; Yanhua Huang (AMB Express)
Abstract D-tagatose, a low-calorie rare sugar, has significant potential in food, medicine, cosmetics, and other industries owing to its high application value and market potential. In this study, Escherichia coli BL21 was used as the starting strain to express the β-galactosidase (β-Gal) gene—BgaB—derived from Bacillus stearothermophilus and the L-arabinose isomerase (L-AI) gene—araA—derived from Thermus sp., yielding the genetically engineered strains E. coli BL21-pET28a-BgaB and E. coli BL21-pET28a-araA. These strains synthesized D-tagatose using β-Gal and L-AI with a conversion rate of 23.73%. Based on this, we constructed a multienzyme cascade pathway comprising β-Gal, L-AI, glucose isomerase (GI), fructose kinase (FK), D-tagatose-bisphosphate aldolase (GatZ), polyphosphate kinase (PPK), and phosphatase (PGP), further enhancing D-tagatose biosynthesis. This multienzyme approach improved the conversion of the intermediate product D-glucose to D-tagatose by 3.84% compared with the dual-enzyme system. Thus, our study provides a theoretical basis and technical support for the industrial production of D-tagatose.